Dopant-Free π-Conjugated Hole Transport Materials for Highly Stable and Efficient Perovskite Solar Cells - Deng, Zhifeng; Cui, Shuaiwei; Kou, Kaichang; Liang, Dongxu; Shi, Xin; Liu, Jinhui (Frontiers in Chemistry, 2021)
Current high efficiency hybrid perovskite solar cells (PSCs) were fabricated with doped hole transfer material (HTM), which showed short-term stability. Doping applied in HTMs for PSCs can enhance the hole mobility and PSCs’ power conversion efficiency, while the stability of PSCs will be significantly decreased due to inherent hygroscopic properties and chemical incompatibility. Development of dopant-free HTM with high hole mobility is a challenge and uttermost important. In this review, a series of selected and typical π-conjugated dopant-free hole transport materials, mainly regarding to small molecules, are reviewed, which could consequently help to further design high performance dopant-free HTMs. In addition, an outline of molecular design concept and also the perspective of ideal dopant-free HTMs were pointed out.